Comparison of zooplankton catches using a Norpac net with 100um and 200um mesh. - Puig, Sahara Joy Belgica (2011.)
The efficiency of a Norpac (North Pacific) net with 100um and 200um mesh sizes in capturing zooplankton in 20 stations along Bicol Shelf from May 20-24, 2008 are described. Overall mean densities were 122.3 ind.m-3 (100 um) and 87.7 indm-3 (200 um). In both mesh sizes, calanoid copepods (29.3 percent in 100 um; 39.3 percent in 200 um) dominated the zooplankters recorded. this was followed by cyclopoid copepods (28.0 percent in 100 um; 28.7 percent in 200 um) and chaetognaths (10.1 percent in 100 um; 10.7 percent in 200 um). The composition and abundance of major zooplankton groups caught in each mesh size were also determined. It appears that overall comparisons of major groups showed that gstropods, harpacticoids, bivalves and siphophores showed significantly higher densities in 100um mesh size.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Norpac net